Analisis Literasi Matematika Mahasiswa Calon Guru SD - Sukmawati Sukmawati (Universitas Veteran Bangun Nusantara, 2023)
Mathematical literacy skills are important to master at this time. Mathematical literacy can help solve real world problems more easily and can compare the various kinds of benefits we will get. Of course mastery is not easy to master just like that without being studied in the world of education. One way is by preparing qualified human resources. Related to this, it is necessary to prepare prospective teachers who have good mathematical literacy as well. This research is a descriptive study with a qualitative approach that aims to describe the mathematical literacy of elementary school teacher candidates in which the results of this study are expected to be able to provide input for the development of teaching materials. Data collection was carried out using test and interview methods. The research results obtained were that subjects with high mathematical literacy were able to fulfill all indicators well, while subjects with medium and low abilities were able to fulfill all indicators but there were still errors in the application of concepts and calculations.